Only pharmacological doses of atrial natriuretic peptide affect intestinal ion transport in non-volume expanded rats. Issue 10 (October 1991) - Lübcke, R; Brunner, J; Hutcheson, F A; Barbezat, G O
Abstract : Pharmacological doses of atrial natriuretic peptide were infused into rats to study its effect on intestinal transport. Saline control or two concentrations of rat alpha atrial natriuretic peptide (0.06 or 1.0 nmol/min/kg) were administered intravenously (1 ml) over one hour. Jejunal net transport of water and electrolytes was measured with a plasma-like luminal electrolyte solution using a 'closed loop' technique. Distal colonic potential difference and arterial blood pressure were monitored continuously. Blood samples for analysis of plasma atrial natriuretic peptide concentrations were taken at the end of the experiments. Plasma concentrations were increased (mean (SD) (2.1 (0.5) and 24.0 (1.1) nmol/l respectively) compared with the controls (0.023 (0.016) nmol/l). Blood pressure dropped by 30% (p less than 0.05) in both groups of rats receiving atrial natriuretic peptide but remained unchanged when control saline was infused. Jejunal net absorption was reduced (p less than 0.01) only in animals receiving the higher concentration of peptide (H2O from 173 (33) to 64 (69) microliters.h-1.cm-2, Na from 25.7 (5.3) to 10.9 (8.9) mumol.h-1.cm-2). Distal colonic potential difference was not affected by atrial natriuretic peptide. In conclusion massive doses of atrial natriuretic peptide are required to produce any change in intestinal salt and water transport in normal, non-volume expanded rats; these effects could be a non-specific or 'toxic' response.